2016
DOI: 10.1534/genetics.116.191197
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effective Population Size from Temporal Allele Frequency Changes in Experimental Evolution

Abstract: The effective population size (Nnormale) is a major factor determining allele frequency changes in natural and experimental populations. Temporal methods provide a powerful and simple approach to estimate short-term Nnormale. They use allele frequency shifts between temporal samples to calculate the standardized variance, which is directly related to Nnormale. Here we focus on experimental evolution studies that often rely on repeated sequencing of samples in pools (Pool-seq). Pool-seq is cost-effective and of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 87 publications
1
46
1
Order By: Relevance
“…A large number of approaches and computer programs are available for estimating effective size from genetic marker data (reviews by e.g., Gilbert & Whitlock, 2015;Luikart et al, 2010;Palstra & Ruzzante, 2008;Wang, 2005Wang, ,2016. Until recently, most studies were based on the "temporal method" that compares allele frequencies in samples collected one or more generations apart to assess variance effective size (N eV ; e.g., Jónás, Taus, Kosiol, Schlötterer, & Futschik, 2016;Jorde & Ryman, 1995,2007Nei & Tajima, 1981;Wang & Whitlock, 2003;Waples, 1989). During the past decade, however, estimation procedures that only require a single sample, collected at one point in time, have become prevailing (Palstra & Fraser, 2012;Waples, 2016).…”
Section: Estimating N E From Empirical Datamentioning
confidence: 99%
“…A large number of approaches and computer programs are available for estimating effective size from genetic marker data (reviews by e.g., Gilbert & Whitlock, 2015;Luikart et al, 2010;Palstra & Ruzzante, 2008;Wang, 2005Wang, ,2016. Until recently, most studies were based on the "temporal method" that compares allele frequencies in samples collected one or more generations apart to assess variance effective size (N eV ; e.g., Jónás, Taus, Kosiol, Schlötterer, & Futschik, 2016;Jorde & Ryman, 1995,2007Nei & Tajima, 1981;Wang & Whitlock, 2003;Waples, 1989). During the past decade, however, estimation procedures that only require a single sample, collected at one point in time, have become prevailing (Palstra & Fraser, 2012;Waples, 2016).…”
Section: Estimating N E From Empirical Datamentioning
confidence: 99%
“…These files were converted to sync format using the mpileup2sync.jar tool from Popoolation2 (Kofler, Pandey, & Schlotterer, 2011). We then estimated effective population size (N e ) using the Nest R package v1.1.9 with three different methods (Jonas, Taus, Kosiol, Schlotterer, & Futschik, 2016). were still significant when adjusted for the number of traits by the Bonferroni procedure.…”
Section: Data Processing and Effective Population Size Estimatesmentioning
confidence: 99%
“…Others have made similar observations on this data. In particular, Jónás et al (2016) showed that the chromosome-wise population size varies even more when it is computed for each replicate separately (see table 1 in Jónás et al 2016). For instance, Ntrue^ is 131 for chromosome 3 R replicate 1, while it is 328 for chromosome X replicate 2.…”
Section: Analysis Of Real Datamentioning
confidence: 99%